2010
DOI: 10.1016/j.eneco.2010.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Macro economy, stock market and oil prices: Do meaningful relationships exist among their cyclical fluctuations?

Abstract: This paper examines the relationship among consumer price index, industrial production, stock market and oil prices in Greece. Initially we use a unified statistical framework (cointegration and VECM) to study the data in levels. We then employ a multivariate VAR model to examine the relationship between the cyclical components of our series. The period of the study is from 1996:1 -2008:6. Findings suggest that oil prices and the stock market exercise a positive effect on the Greek CPI, in the long run. Cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(97 citation statements)
references
References 73 publications
(76 reference statements)
2
85
2
3
Order By: Relevance
“…Since the seminal paper by Hamilton (1983), mounting empirical evidence indicates that oil prices exercise a strong negative influence on the economy. More specifically, past evidence suggest that there are significant effects of oil prices on industrial production and inflation (see, inter alia, Filis and Chatziantoniou, 2013;Balke et al, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Peter Ferderer, 1997). Furthermore, authors such as, Rahman and Serletis (2011), Elder and Serletis (2010), Cologni and Manera (2008), Cunado and Pérez de Gracia (2005), Lee et al (1995) and Hamilton (1983) confirm that the US economic activity has been significantly affected by rises in oil prices, as well as, by the uncertainty about future oil price changes.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Since the seminal paper by Hamilton (1983), mounting empirical evidence indicates that oil prices exercise a strong negative influence on the economy. More specifically, past evidence suggest that there are significant effects of oil prices on industrial production and inflation (see, inter alia, Filis and Chatziantoniou, 2013;Balke et al, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Peter Ferderer, 1997). Furthermore, authors such as, Rahman and Serletis (2011), Elder and Serletis (2010), Cologni and Manera (2008), Cunado and Pérez de Gracia (2005), Lee et al (1995) and Hamilton (1983) confirm that the US economic activity has been significantly affected by rises in oil prices, as well as, by the uncertainty about future oil price changes.…”
Section: Introductionmentioning
confidence: 71%
“…On one hand, higher oil prices exert negative impacts on the economy, such as lower productivity and/or higher inflation (see, inter alia, Filis and Chatziantoniou, 2013;Montoro, 2012;Natal, 2012;Rahman and Serletis, 2011;Balke et al, 2010;Elder and Serletis, 2010;Tang et al, 2010;Du et al, 2010;Filis, 2010;Cologni and Manera, 2008;Cunado and Pérez de Gracia, 2005;Peter Ferderer, 1997;Hamilton, 1983). Such economic conditions put pressure on policy makers to mitigate the negative effects of increased oil prices, which in turn, raises concerns regarding the success of these policies.…”
Section: Resultsmentioning
confidence: 99%
“…This negative relationship between oil prices and stock returns has also been documented by Filis (2010) (2001) and Gjerde and Saettem (1999). Nandha and Brooks (2009) suggest that the effect of oil prices on stock market returns depends on the country's characteristics and the sector of the economy.…”
Section: Oil Price Effect On the Stock Marketmentioning
confidence: 81%
“…The results found that macroeconomic variables significantly influence stock market indices. However, the VEC equilibrium time-series model applied by others (Adeleke and Gbadebo, 2012;Agrawalla and Tuteja, 2008;Chaudhuri and Smiles, 2004;Filis, 2010;Herve et al, 2011;Hess, 2004;Hosseini et al, 2011;Karacaer and Kapusuzoglu, 2010;Kyereboah and Agyire, 2008;Maysami and Koh, 2000;Muradoglu et al, 2001;Nasseh and Strauss, 2000;Patra and Poshakwale, 2006;Wong et al, 2006) to explore the long-run and short-run equilibrium relationships between macroeconomic variables and stock market indices. These studies revealed that macroeconomic variables significantly change stock market indices.…”
Section: Review Of Previous Empirical Studiesmentioning
confidence: 99%